Effects of critical factors on growth and survival of seahorse juveniles, Hippocampus barbouri (Jordan & Richardson,1908) - Er, Vivian Wei Chee (2019)
Seahorse under the genus Hippocampus, has a total of 44 species worldwide. Its unique features which include horse-like head, kangaroo-like pouch and monkey-like tail, made it much sought after by the ornamental fish industry. Seahorses contribute ecologically, economically, and culturally to the human kind. However, the overexploitation of seahorses for traditional Chinese medicine (TCM), aquarium trade and curios resulted in the rapid decline of wild seahorse population. Seahorse aquaculture has been proposed as one of the solution to reduce stress on wild stock as well as to support the TCM industry. However, maintaining survival of seahorse juveniles in captive condition proved to be quite a challenge. Production techniques have been developed for very few species but yet to achieve their optimal rearing conditions. Rearing conditions namely critical factors were not well studied. Hence, the objectives of this study were to compare the growth and survival of H. barbouri juveniles under different conditions. Factors considered include nursing duration, water surface flow rate, stocking density, temperature, salinity, photoperiod, light intensity and feeding. Different ages of H. barbouri juveniles were used to determine the most suitable day to be transferred from nursing tank into rearing tank. Hippocampus barbouri juveniles of 3, 5, 7 and 9 day-old were used for this experiment. Upon completion, a follow up study on 9, 12 and 15 day-old H. barbouri juveniles were used to determine the best day to transfer juveniles from nursing tank to rearing tank. Hippocampus barbouri juveniles that nursed for 9 days before transferred to rearing tank were found to have the best growth and survival compared to other treatments. Results from the follow up experiment showed that H. barbouri juveniles nursed for 12 days has the best survival. Hence, all other experiments were conducted using 12 day- old H. barbouri juveniles. For experiment on surface water flow rate, three flow rate 0.056, 0.077 and 0.143 m/s were used. At the end of study, the lowest flow rate 0.056 m/s showed the best growth and survival. Stocking density of 0.3, 0.4 and 0.5 juv/L were used to determine the best stocking density for H. barbouri juveniles. Results show no significant difference (p>0.05) for growth. While stocking density of 0.5 juv/L showed the best survival (p<0.05) of H. barbouri juveniles. As for experiment on temperature, three temperatures used were 25, 28 and 31 °C. Results showed that H. barbouri juveniles cultured at 25 °C showed the best growth and survival. For experiment on salinity, 25, 30 and 35 ppt were tested. Growth and survival of H. barbouri juveniles were the best when cultured at 30 ppt. Photoperiod used in this study were 8L:16D, 12L:12D and 16L:8D. Results showed that photoperiod of 12L:12D produced the best height and weight of H. barbouri juveniles with 37.71 mm and 0.165g, with survival of 80%. As for experiment on light intensity, natural light with intensity of 700 lx, fluorescent light 1400 lx and LED light 2100 lx were used. At the end of study period, light intensity of 1400 and 2100 lx resulted in best growth and survival of H. barbouri juveniles. Feeding experiment was conducted to determine the best Artemia enrichment for growth and survival of H. barbouri juveniles. Three treatments used were newly hatched Artemia nauplii, Artemia enriched with marine fish pellet and Artemia enriched with cod liver emulsion. Growth and survival of H. barbouri juveniles fed with Instar II Artemia enriched with cod liver emulsion showed significantly better results (p<0.05) when compared to all other two treatments. To conclude, the critical factors determined in the current study may aid aquaculturist, particularly those interested in the culture of this unique species. In addition, the success in seahorse aquaculture, may directly benefits the ornamental fish industry for sustainable supply of seahorses.